A Note on Eucalyptus Plantations in Old Mysore State - Nanjundappa, D. (Indian Forester, 1957)
In the north-western part of Mysore State, Eucalptus citriodora plantations were formed from 1937 to 1951 by sowing seeds at a cost of Rs. 73-8-0 per acre. Finding that the stocking is not uniform in the plantations raised by sowing seeds, the technique of sowing was changed to planting from 1952. The cost of formation per acre by planting Eucalyptus transplants is Rs. 54-3-0. In the eastern part of Mysore State, there are some old Eucalyptus trees of different species on Nandi Hills. The seeds collected from these mother trees were mixed and used for raising Eucalyptus plantations on a small scale from 1937 by planting Eucalyptus transplants (naked) up to 1951. Casuarina plantations were being formed on a large scale before 1951. Finding that Eucalyptus puts on more height and girth compared to casuarina, from 1952, planting of casuarina is given up by the Forest Department and Eucalyptus plantations on a large scale are being formed. The cost of formation per acre in country ploughed area is Rs. 39 and in tractor ploughed and trenched area is Rs. 77-12-0. The total area of Eucalyptus plantations formed up to end of 1956 in Mysore State is 5,318Â½ acres.